The impact mechanism of network diversity on innovation performance in the manufacturing industry: The roles of entrepreneurial strategy, relational embedding, and government support - Yu, Daining (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of network diversity on innovation performance, examining the mediating role of entrepreneurial strategy in the relationship between network heterogeneity and innovation performance. It also explores the moderating effect of relational embeddedness on the link between network diversity and innovation performance, as well as the moderating effect of government support on the relationship between entrepreneurial strategy and innovation performance. A total of 488 manufacturing enterprises were selected as the research sample. Data were collected via online questionnaires distributed through WeChat and other group channels, with five questionnaires issued to each enterprise. In total, 2,440 questionnaires were distributed, and 1,842 valid responses were collected. The results reveal that network heterogeneity has a significant positive effect on innovation performance; network heterogeneity also positively influences entrepreneurial strategy; entrepreneurial strategy exerts a significant positive impact on innovation performance; entrepreneurial strategy plays a significant mediating role between network heterogeneity and innovation performance; relational embeddedness significantly moderates the relationship between network heterogeneity and innovation performance; and government support significantly moderates the relationship between entrepreneurial strategy and innovation performance.